PARTICIPATION IN INTERNATIONAL EXCHANGE PROGRAM: CONTRIBUTIONS OF THE EXPERIENCE OF SANDWICH-UNDERGRADUATE STUDIES IN NURSING - Renata de Moura Bubadué; Franco Carnevale; Cristiane Cardoso de Paula; Stela Maris de Mello Padoin; Eliane Tatsch Neves (Universidade Federal de Santa Maria, 2013)
http://dx.doi.org/10.5902/217976927922 Aim: to describe the experience of a Nursing Undergraduate student in an international exchange program in Canada. Methodo: The exchange happened through the awarding of a scholarship from the Brazilian government Science without Boarders Program, between the Federal University of Santa Maria/RS/Brazil and McGill University, in Montreal/Quebec/Canada. It was conducted from march to august 2012, with Graduate and Undergraduate Programs in diverse fields of child and adolescent health. Results: activities in research groups, courses, lectures and research projects focused on palliative care, bioethics and qualitative approaches in research. Final Considerations: This experience enabled academic, personal and social development, as well as the beginning of constructing a research network, contributing to exchange among researchers and the process of internationalization of Nursing.